The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1161/circimaging.120.010628
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cardiac Fibroblast Activation Protein Activity by Positron Emission Tomography and Cardiovascular Disease

Abstract: Background: FAP (fibroblast activation protein) plays an important role in cardiac wound healing and remodeling. Although initially developed as a theranostic ligand for metastasized cancer, FAPI (FAP inhibitor) tracers have recently been used to study cardiac remodeling following myocardial infarction in small-animal models. The aim of the study was to evaluate the activity of FAP via FAPI–positron emission tomography–computed tomography scans in human hearts. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 25 publications
6
85
2
1
Order By: Relevance
“…Increased FAP has reportedly been found in refractory rheumatoid arthritis [20]. Besides renal brosis, high intake of FAPI has been found in benign diseases such as liver brosis, arthritis, cardiovascular disease, Crohn's bowel disease, idiopathic retroperitoneal brosis, pancreatitis, and osteophytes [21][22][23][24][25][26][27][28]. The diagnostic utility of [ 68 Ga]Ga-FAPIs needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Increased FAP has reportedly been found in refractory rheumatoid arthritis [20]. Besides renal brosis, high intake of FAPI has been found in benign diseases such as liver brosis, arthritis, cardiovascular disease, Crohn's bowel disease, idiopathic retroperitoneal brosis, pancreatitis, and osteophytes [21][22][23][24][25][26][27][28]. The diagnostic utility of [ 68 Ga]Ga-FAPIs needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Derived from the pathomechanism, myocarditis in general and fibrosis in terms of cardiomyopathy might be detectable by FAPI PET/CT, as they are based on inflammation and tissue remodeling. Recently, it was shown that diabetes is associated with elevated tracer enrichment in FAPI PET/CT in the heart ( 17 ). This was associated with an enrichment of tracer accumulation within all segments of the left ventricle, whereas patients with ICI-associated myocarditis revealed a localized enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…High left ventricular FAP signal intensities as measured by positron-emission-tomography are associated with cardiovascular and metabolic risk factors such as hypertension, diabetes mellitus and obesity [ 35 ]. Moreover, advances have been made using therapies depleting FAP cells to treat cancer disease, which could potentially affect the heart [ 16 , 36 ].…”
Section: Discussionmentioning
confidence: 99%